Pelatihan Google Form Sebagai Media Survey Kepuasan Pelanggan - Gustiana, Zelvi; Welnof Satria; Afriadi Amin; Endri Dores (Jurnal Pengabdian Masyarakat, 2022)
Information technology is a general term for anything related to anything that assists humans in creating, modifying, storing, managing or disseminating information. . The development of technology at this time is very rapid and has an impact on all aspects of people's lives, one of which is in the field of business and business. Currently there are many business people who apply technology in running their business, both in making efforts, storing data, and evaluating efforts. One form of the application of information technology is to measure customer satisfaction in online businesses in the fashion sector. The service carried out is training on the use of Google Forms as a medium for customer satisfaction when making purchases at the Online Fashion Store. Online shop customers will provide questions in the form, related to products and services. The training carried out is by providing an explanation about Google Forms and mentoring the owner and admin. The results of this dedication can be applied by online stores and can be used for evaluation of online fashion stores. This is aimed at fashion online stores in improving the quality of online stores.